Cross-cultural analysis of the paleonym “pearl” - Turaeva, Maftuna Boboyorovna (Science and Education, 2023)
The article discusses the paleonym “pearl” as it is understood in different cultures. References to specific cultural contexts or traditions are identified in which the pearl has particular significance. This might include references to mythology, folklore, or religious traditions. The article highlights similarities and differences in cultural attitudes toward the word “pearl”. This involves identifying cultural practices or beliefs related to the use, ownership, or symbolism of pearls, and comparing these practices across different cultures.